SISTEM INFORMASI SDN 190 BENGKULU UTARA BERBASIS WEB - Ransesta, Lingga; Handayani, Sri; Gunawan, Gunawan; Andilala, Andilala (UNIVERSITAS STEKOM, 2025)
This study aims to design and develop a web-based information system at SDN 190 Bengkulu Utara to improve the efficiency of information delivery between the school and parents and the community. This information system is designed to address the main problems that the school has faced, namely delays, inaccessibility, and miscommunication in information delivery due to the use of manual methods such as printed letters and verbal notifications. This study uses a normative method with a qualitative approach through observation, interviews, and literature studies to analyze needs and determine the features required in the system. The results of the needs analysis process indicate that the school desperately needs digital media that can display information such as school profiles, announcements, teacher data, organizational structures, class data, school news, and visual documentation in the form of photo galleries. These features are designed in an easy-to-use system structure with a simple yet functional interface, so that it can be operated by even non-technical users. This system is also equipped with a login page and admin dashboard to manage and update content flexibly and securely. Based on testing using the blackbox method, all features run well and are in accordance with user needs. This study concludes that the developed web-based information system has succeeded in improving communication efficiency and transparency within SDN 190 Bengkulu Utara.